Relationship between Blood Lead Level and Intelligence Quotient in School Age Children at Klity Village, Thongphaphum District, Kanchanaburi Province - Wachsuwanmanee, Nuanchan; Sareewong, Chomlanade; Phasug, Thanyalak; Howha, Manoros; Pannak, Nisarat; Sudsawaeng, Valeetip (Journal of Health Science of Thailand, 2017)
The purpose of this analytical cross-sectional study was to investigate blood lead level (BLL) and study the relationship between blood lead levels and children’s intelligence quotient (IQ) in exposed area (Klity village) (Banthungsueathon school and Banklitylang school) compared with that of children outside the contaminated areas (Banlintin school and Banplilokkhi school, during March to June 2017. IQ was assessed by the Standard Progressive Matrices (SPM; parallel version). The subjects were given general information and risk factor questionnaire. The BBL was analized by atomic absorption spectrometry. Data were analyzed by means of descriptive statistics: percentage, mean, standard deviation; and inferential statistics using independent t-test, ANOVA, chi-square and Pearson correlation. There were altogether 623 students with the age range of 6 and 18 years and the mean age of 10.65 years. They were 299 male (47.99%) and 324 female (52.01%). The mean BLL was 7.07 µg/dl (ranging from 0.25 to 33.80 µg/dl); and 24.56% of students (n=153) had BLL > 10 µg/dl whereas 75.44% (n=470) had <10 µg/dl. The mean IQ was 89.56 points; and 49.34% of the students (n= 298) had IQ below 90 points. Among the students with BLL <10 µg /dl, 44.74% (n=204) had IQ below 90 campared to 63.51% (n=94) in students with BLL >10 µg/dl (p<0.01). Furthermore, 59.13% of student in exposed area (Klity village) had IQ <90 compared to 44.19% among students outside the area (p<0.01). Therefore, it could be concluded that students in this study who were exposed to lead in the environment had high blood lead level which was found to be associated with the low intellectual level